2021
DOI: 10.3390/cells10082087
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Induced Overexpression of TGFβ and PODXL Contributes to Colorectal Cancer Cell Radioresistance through Enhanced Motility

Abstract: The primary cause of colorectal cancer (CRC) recurrence is increased distant metastasis after radiotherapy, so there is a need for targeted therapeutic approaches to reduce the metastatic-relapse risk. Dysregulation of the cell-surface glycoprotein podocalyxin-like protein (PODXL) plays an important role in promoting cancer-cell motility and is associated with poor prognoses for many malignancy types. We found that CRC cells exposed to radiation demonstrated increased TGFβ and PODXL expressions, resulting in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Similar to the traditional view, after JQ-1 treatment, the expression of many oncogenes was downregulated, but we also found abnormally high expression of several key genes that may lead to acquired resistance to JQ-1. PubMed and Web of Science were used to explore the biological roles of TSGA10, FOS, FGF18, MGAT5, EFNB2, and PODXL in cancer research [ [40] , [41] , [42] ]. However, only a small number of cancer studies have focused on these specific genes, which limits our further research.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the traditional view, after JQ-1 treatment, the expression of many oncogenes was downregulated, but we also found abnormally high expression of several key genes that may lead to acquired resistance to JQ-1. PubMed and Web of Science were used to explore the biological roles of TSGA10, FOS, FGF18, MGAT5, EFNB2, and PODXL in cancer research [ [40] , [41] , [42] ]. However, only a small number of cancer studies have focused on these specific genes, which limits our further research.…”
Section: Discussionmentioning
confidence: 99%
“…1a). It was found that radiation-resistant CRC increased the expression of TGF-β and the cell surface glycoprotein podocalyxin-like protein (PODXL) to promote tumor invasion and metastasis [23]. Furthermore, CRC patients with high TGF-β and PODXL expression have been shown to have worse prognosis [24][25][26].…”
Section: Tumor Ecmmentioning
confidence: 99%
“…Association studies suggested that PODXL is a potential biomarker for cancer diagnosis and prognosis in multiple cancers ( Borg et al., 2016 ; Kusumoto et al., 2017 ; Lee et al., 2017 ; Taniuchi et al., 2018 ; Zhang et al., 2019 ; He et al., 2020 ). In addition, PODXL plays important role in cancer metastasis by promoting cell migration ( Lin et al., 2014 ; Kusumoto et al., 2017 ; Lee et al., 2017 , 2021 ), cell invasion ( Wu et al., 2013 ; Lin et al., 2014 ; Chan et al., 2016 ; Kusumoto et al., 2017 ), cell extravasation ( Fröse et al., 2018 ), immune evasion ( Amo et al., 2015 ), and chemoresistance ( Huang et al., 2015 ; Zhou et al., 2015 ; Lee et al., 2017 ; Tamayo-Orbegozo et al., 2020 ). Therefore, PODXL is also a valuable therapeutic target for cancer metastasis ( Snyder et al., 2015 ; Chijiiwa et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%